Pengaruh Work-Life Balance dan Gaji Terhadap Kesejahteraan Pegawai Kantor Bupati Kubu Raya - Marlina, Marlina; Firayanti, Yuni; Marhamah, Marhamah (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This study aims to analyze (1) the effect of Work-Life Balance on employee well-being at the Regent Office of Kubu Raya, and (2) the effect of salary on employee well-being at the Regent Office of Kubu Raya. The research employed a quantitative method with an associative approach. Primary data were collected through the distribution of Likert-scale questionnaires to 144 respondents selected using proportional random sampling based on the Slovin formula from a total population of 226 employees. Data analysis was conducted through validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that Work-Life Balance has a positive and significant effect on employee well-being. Employees who are able to balance work and personal life tend to have lower stress levels, higher job satisfaction, and better psychological conditions. The salary variable also has a positive and significant effect on employee well-being. Fair, adequate, and timely salary payments increase financial security, work motivation, and organizational loyalty. Simultaneously, Work-Life Balance and salary significantly affect employee well-being with a coefficient of determination of 36.3%. This implies that both variables explain 36.3% of the variation in employee well-being, while the remaining 63.7% is influenced by other factors not examined in this study.